A New Case of de novo Variant c.892C>T (p.Arg298Trp) in NACC1: A First Case Report From China - Lyu, Baiyu; Dong, Yan; Kang, Juan (Frontiers in Pediatrics, 2021)
Background: The nucleus accumbens associated 1 (NACC1 ) gene is a member of the BTB/POZ family of transcription factors. A de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1 may define a syndrome characterized by intellectual disability, infantile epilepsy, congenital cataract, and feeding difficulties. Case presentation: We report a new case with a neurodevelopmental disorder characterized by severe intellectual disability, infantile epilepsy, congenital cataract, and feeding difficulties. Brain MRI reveals brain dysplasia. We observe a de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in this case. Now, the child regularly goes to the hospital for rehabilitation training (once a month). Sodium Valproate (10mg/kg.d) and Clobazam (10mg/kg.d) are used in the treatment of epilepsy.The search revealed 2 articles related to a syndrome caused by a de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1; they were screened main clinical features of 8 cases of a syndrome were summarized and analyzed. Conclusions: NACC1 gene is a member of the BTB/POZ family of transcription factors and has not previously been associated with Mendelian phenotypes. A de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1 may define a syndrome characterized by intellectual disability, infantile epilepsy, congenital cataract, and feeding difficulties. At present, there is no effective cure method. In the future, we need more cases to determine the phenotype-genotype correlation of NACC1 variants. Future transcriptional studies may further clarify this rare, recurrent, and could potentially lead to targeted therapies.